Patient satisfaction with the work of nurses in primary health care - Franjo, Jasminka (Array, 2020)
Introduction. Patient satisfaction with provided health care is an important indicator of health care quality. Research on patient satisfaction has been very frequent in recent years. Aim. A prospective, cross-sectional study was conducted at the Health Centre of the Ministry of the Interior of the Republic of Croatia between April and June 2019. The aim of this study was to examine the satisfaction of patients with the work of nurses in primary health care. Methods. A standardized Nursing Practitioner Satisfaction Survey questionnaire, for which we received the author’s approval, was used. The study involved 200 patients from the Health Centre of the Ministry of the Interior of the Republic of Croatia. Patients who came to the Health Centre’s outpatient clinics requiring only the services of nurses were included in the study. Out of 200 patients surveyed, 185 questionnaires were filled out correctly, while 15 were filled out incorrectly. Results. Patients from the Health Centre of the Ministry of the Interior of the Republic of Croatia are satisfied with the work of nurses in primary health care. There is no statistically significant difference in the satisfaction with the work of nurses in primary health care according to gender, education, marital or working status. There is a statistically significant difference in patient satisfaction with the work of nurses according to the respondents’ age, where respondents in the age group between 26 and 40 years are less satisfied (Kruskal-Wallis test, Me=3.8). There is a statistically significant difference in the satisfaction of patients with the work of nurses in primary health care according to the respondents’ annual income, where satisfaction is more pronounced among respondents with an annual income between 26.000 to 35.000 HRK and in the range between 36.000 to 45.000 HRK (Kruskal-Wallis test, p<0.01).